2010
DOI: 10.1098/rstb.2010.0146
|View full text |Cite
|
Sign up to set email alerts
|

Punishment and spite, the dark side of cooperation

Abstract: Causing harm to others would hardly seem to be relevant to cooperation, other than as a barrier to it. However, because selfish individuals will exploit cooperators, functional punishment is an effective mechanism for enforcing cooperation by deterring free-riding. Although functional punishment can shape the social behaviour of others by targeting non-cooperative behaviour, it can also intimidate others into doing almost anything. Second-party functional punishment is a self-serving behaviour at the disposal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
168
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 159 publications
(226 reference statements)
9
168
0
1
Order By: Relevance
“…Indeed, experiments reveal that they will do this even when it is costly to themselves (Gintis 2011, Ch 3.6). This proclivity for punishment is further underscored by neurobiological evidence suggesting that punishment activates parts of the brain's reward circuit and so is likely to feel pleasurable (Jensen 2010;Pinker 2011, 529-532). 5 There are many criminal theorists who support this basic position: Michael Moore (1993;1997); Larry Alexander and Kimberly Ferzan (2006); and Antony Duff (2007).…”
Section: The Argument For the Retribution Gapmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, experiments reveal that they will do this even when it is costly to themselves (Gintis 2011, Ch 3.6). This proclivity for punishment is further underscored by neurobiological evidence suggesting that punishment activates parts of the brain's reward circuit and so is likely to feel pleasurable (Jensen 2010;Pinker 2011, 529-532). 5 There are many criminal theorists who support this basic position: Michael Moore (1993;1997); Larry Alexander and Kimberly Ferzan (2006); and Antony Duff (2007).…”
Section: The Argument For the Retribution Gapmentioning
confidence: 99%
“…Support for this comes from experimental work and from the evolutionary and ethnographic record (Carlsmith and Darley 2008;Jensen 2010). The experimental work is particularly instructive.…”
Section: The Argument For the Retribution Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Males, and alloparents in general, may increase their fitness by influencing the behavior of conspecifics in their social group, as they would when disciplining another dolphin. Studies on punishment in humans and primates have suggested that punishment evolved as a way to encourage cooperation and reduce selfish behavior in social groups (Boyd, Gintis, & Bowles, 2010;Gardner & West, 2004;Jensen, 2010;Riedl, Jensen, Call, & Tomasello, 2012;Seymour, Singer, & Dolan, 2007). A review of punishment in animal groups (Clutton-Brock & Parker, 1995) suggested that punishment from a dominant animal to a subordinate can increase the dominant animal's fitness.…”
Section: Description Of Participantsmentioning
confidence: 99%
“…Short chases may also be related to the threat of discipline that a chase implies. In some cooperatively breeding animals, dominant individuals maintain cooperation and order in their society through the threat of costly punishment to an uncooperative individual (Jensen, 2010;Wong, Buston, Munday, & Jones, 2007). Subdominant individuals in the population may choose to limit the frequency of unpopular behaviors to avoid being attacked or exiled from their social group or denied other social and reproductive benefits (Balshine-Earn, Neat, Reid, & Taborsky, 1997;Johnstone & Cant, 1999;Wong et al, 2007).…”
Section: Success In Disciplinementioning
confidence: 99%